Validating Motivation, Intention, and Behavior of Muslim Tourists from East Java: A Confirmatory Factor Analysis Approach - Endah Setyowati; Ellyvia Abiani; Almira Ivah Edina (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2026)
This study aims to validate the constructs of travel motivation, travel behavior, and travel intention among Muslim tourists from East Java in the context of traveling to Muslim-friendly tourist destinations in Indonesia. The study used a quantitative approach with primary data obtained through questionnaires from 97 respondents who had traveled to several Muslim-friendly destinations in Indonesia. Data analysis was conducted using Confirmatory Factor Analysis (CFA) to test the validity and reliability of the constructs through evaluating convergent validity, discriminant validity, and indicator reliability. The results showed that all constructs met the recommended validity and reliability criteria. The findings also indicate that tourist motivation and behavior play an important role in shaping travel intentions to halal destinations. The main motivations of tourists include the desire for self-development, seeking tranquility, and enjoying natural beauty, while travel behavior is influenced by perceived ease of travel, social norms, and positive attitudes towards halal tourism, which is in line with the Theory of Planned Behavior framework. Overall, religious motivation and halal tourism experiences play an important role in strengthening the intention of Muslim tourists from East Java to visit and recommend Muslim-friendly destinations in Indonesia.